Indian Adolescent Mental Health - United States. Congress. Office of Technology Assessment. (United States. Congress. Office of Technology Assessment., 1990)
This report reviews the mental health needs of Indian adolescents (those of American Indian and Alaska Native descent) and the services available to them. It summarizes the findings of the review, suggests options that Congress might consider, and provides an overview of other special health needs of adolescents (ages 10 to 18).